SISTEM PENDUKUNG KEPUTUSAN PENENTUAN SISWA BERPRESTASI MENGGUNAKAN METODE PROFILE MATCHING DI SMK NEGERI 1 SEI KEPAYANG - Delyanti Putri Sitorus; Bambang Irwansyah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: SMK Negeri 1 Sei Kepayang is a vocational high school that grants awards to outstanding students in every assessment period. However, the selection of outstanding students is still carried out manually and considers only report card scores, making the assessment subjective, time-consuming, and prone to error. To overcome this problem, a Decision Support System (DSS) was developed using the Profile Matching method, which compares each student's actual profile with an ideal profile determined by the school. The data used consists of 101 twelfth-grade students spread across four classes (XII TSM, XII APHP, XII RPL 1, and XII RPL 2) with five criteria in two aspects, namely the academic aspect (average report card score, productive/competency assessment score, and Competency Certification Examination score) and the extracurricular aspect (Scouts and Futsal). The processing stages include GAP value calculation, weight-value conversion, grouping into Core Factor and Secondary Factor, calculation of each aspect's value, and finally the final value and ranking. The system was developed as a web-based application using the PHP programming language and a MySQL database, then tested using Blackbox Testing. The test results show that the Profile Matching method is able to produce an objective student ranking, with 4 students in the Very Suitable category, 25 students Suitable, and 72 students Not Suitable. The student with the highest final score is Siti Patima Sari Harahap with a score of 4.4 in the Very Suitable category. This ranking result can be used by the school as evaluation material for determining outstanding students objectively, transparently, and accountably.   Keywords: decision support system, profile matching, outstanding student, PHP, web   Abstrak: SMK Negeri 1 Sei Kepayang merupakan sekolah menengah kejuruan yang memberikan penghargaan bagi siswa berprestasi pada setiap periode penilaian. Namun, proses penentuan siswa berprestasi masih dilakukan secara manual dan hanya mempertimbangkan nilai rapor sehingga penilaian cenderung subjektif, memerlukan waktu lama, serta rentan kesalahan. Untuk mengatasi permasalahan tersebut, dibangun sebuah Sistem Pendukung Keputusan (SPK) menggunakan metode Profile Matching yang membandingkan profil aktual setiap siswa dengan profil ideal yang telah ditetapkan sekolah. Data yang digunakan adalah 101 siswa Kelas XII yang tersebar pada empat kelas (XII TSM, XII APHP, XII RPL 1, dan XII RPL 2) dengan lima kriteria pada dua aspek, yaitu aspek akademik (nilai rata-rata rapor, nilai produktif/asesmen kompetensi, dan nilai UKK) serta aspek ekstrakurikuler (Pramuka dan Futsal). Tahapan pengolahan meliputi perhitungan nilai GAP, konversi bobot nilai, pengelompokan Core Factor dan Secondary Factor, perhitungan nilai tiap aspek, hingga nilai akhir dan perangkingan. Sistem dibangun berbasis web menggunakan bahasa pemrograman PHP dan basis data MySQL, kemudian diuji menggunakan Blackbox Testing. Hasil pengujian menunjukkan bahwa metode Profile Matching mampu menghasilkan peringkat siswa secara objektif dengan kategori Sangat Sesuai sebanyak 4 siswa, Sesuai sebanyak 25 siswa, dan Tidak Sesuai sebanyak 72 siswa. Siswa dengan nilai akhir tertinggi adalah Siti Patima Sari Harahap dengan nilai 4,4 berkategori Sangat Sesuai. Hasil perangkingan ini dapat dijadikan bahan evaluasi bagi pihak sekolah dalam menentukan siswa berprestasi secara objektif, transparan, dan dapat dipertanggungjawabkan. Kata Kunci: sistem pendukung keputusan, profile matching, siswa berprestasi, PHP, web.